2017
DOI: 10.1523/eneuro.0040-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Histone Hypervariants H2A.Z.1 and H2A.Z.2 Play Independent and Context-Specific Roles in Neuronal Activity-Induced Transcription ofArc/Arg3.1and Other Immediate Early Genes

Abstract: The histone variant H2A.Z is an essential and conserved regulator of eukaryotic gene transcription. However, the exact role of this histone in the transcriptional process remains perplexing. In vertebrates, H2A.Z has two hypervariants, H2A.Z.1 and H2A.Z.2, that have almost identical sequences except for three amino acid residues. Due to such similarity, functional specificity of these hypervariants in neurobiological processes, if any, remain largely unknown. In this study with dissociated rat cortical neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 51 publications
4
38
0
Order By: Relevance
“…H2A.Z accumulated primarily in exons and 5’UTR regions, with minimal changes occurring in introns, intergenic regions, and non-coding RNA (Figure 2b). A GO enrichment analysis revealed H2A.Z accumulation in categories that include positive and negative regulators of transcription, as well as ubiquitin protein ligase activity (Figure 2e), consistent with a recent study demonstrating H2A.Z-mediated regulation of the ubiquitin proteasome system (Dunn et al, 2017). Combined with evidence for age-related accumulation of H3.3 (Maze et al, 2015), our data suggest that the composition of histone subtypes that make up nucleosomes is subject to age-related changes, which may influence the overall chromatin landscape in aged mice.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…H2A.Z accumulated primarily in exons and 5’UTR regions, with minimal changes occurring in introns, intergenic regions, and non-coding RNA (Figure 2b). A GO enrichment analysis revealed H2A.Z accumulation in categories that include positive and negative regulators of transcription, as well as ubiquitin protein ligase activity (Figure 2e), consistent with a recent study demonstrating H2A.Z-mediated regulation of the ubiquitin proteasome system (Dunn et al, 2017). Combined with evidence for age-related accumulation of H3.3 (Maze et al, 2015), our data suggest that the composition of histone subtypes that make up nucleosomes is subject to age-related changes, which may influence the overall chromatin landscape in aged mice.…”
Section: Resultssupporting
confidence: 90%
“…Consistent with those findings, we now show that Arc (Virus × Training interaction: F 1,15 = 7.39, p = 0.02) expression is also elevated 1h after fear conditioning in H2A.Z-depleted mice. Such bidirectional effects of H2A.Z depletion were previously reported (Dunn et al, 2017, Weber et al, 2014), and suggest that H2A.Z can promote or repress learning-induced gene expression, while producing minimal effects on basal transcription.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In DT40 chicken cells, knock-out of H2A.Z.2 results in a slower cell proliferation rate compared to the wild type and H2A.Z.1 knock-out cells 26 , while in humans, Floating-Harbor syndrome 27 and malignant melanoma 28 have been specifically linked to H2A.Z.2 27 . In addition, both variants seem to play independent roles in the transcription of some genes involved in the response to neuronal activity 29 . Moreover, very recently, it was shown that the differences between H2A.Z.1 and H2A.Z.2 on transcription regulation seems to depend more on the relative level of the two paralogues rather than on their chromatin localisation 30 .…”
Section: Introductionmentioning
confidence: 99%